FITOPLANKTON PADA HABITAT IKAN CEMPEDIK (Osteochilus spilurus) DI SUNGAI LENGGANG, BELITUNG TIMUR - Jeny Setiawan; Ardiansyah Kurniawan; Suci Puspita Sari; Andri Kurniawan; Yulian Fakhrurrozi (Samakia : Jurnal Ilmu Perikanan, 2018)
Lenggang River in East Belitung regency becomes the natural habitat of Cempedik Fish (Osteochilus spilurus) which is an important economical plankton-feeder fish and has close to the culture of society. The production which still dependent of natural catch makes the description of phytoplankton can be the foundation in fisheries management and developing aquaculture of Cempedik Fish. This study aims to obtain a description of phytoplankton in Lenggang River using quantitative descriptive method. Phytoplankton sampling was conducted during the Cempedik Fishing season in December 2016 with four stations on the Lenggang River based on Cempedik Fish catching location. The abundance of phytoplankton showed values ​​between 3,710 - 8,676 individuals / liter and correlated with the location of Cempedik Fish catch. The dominant index of phytoplankton showed a low value (0.16-0.21) and the uniformity index at the moderate level (0.66 - 0.79) with the Bacillariophyceae Class having the highest dominance.